2017
DOI: 10.1039/c6gc02349e
|View full text |Cite
|
Sign up to set email alerts
|

Nitrate reduction on the surface of bimetallic catalysts supported by nano-crystalline beta-zeolite (NBeta)

Abstract: A nano-crystalline beta zeolite supported bimetallic catalyst was developed and evaluated for the complete and selective reduction of nitrate to environmentally friendly nitrogen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(11 citation statements)
references
References 36 publications
0
11
0
Order By: Relevance
“…In a typical experiment, 100 mL of synthetic solution of NaNO 3 containing 100 mg/L of nitrates ( ) were purged by nitrogen gas at a flow rate of 100 mL/min for 20 min prior to the test, in order to remove the excess oxygen. Aqueous solution of (0.01 mM) NaBH 4 was prepared in presence of sodium hydroxide (0.2%) and then 0.1 g of catalyst in a powder form was reduced by adding dropwise followed by vacuum-filtration [ 32 ]. The reduced catalyst was washed with Milli-Q water twice to remove residual chemicals and immediately transferred to the reactor.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a typical experiment, 100 mL of synthetic solution of NaNO 3 containing 100 mg/L of nitrates ( ) were purged by nitrogen gas at a flow rate of 100 mL/min for 20 min prior to the test, in order to remove the excess oxygen. Aqueous solution of (0.01 mM) NaBH 4 was prepared in presence of sodium hydroxide (0.2%) and then 0.1 g of catalyst in a powder form was reduced by adding dropwise followed by vacuum-filtration [ 32 ]. The reduced catalyst was washed with Milli-Q water twice to remove residual chemicals and immediately transferred to the reactor.…”
Section: Methodsmentioning
confidence: 99%
“…The detection of the sample was achieved with a diode array detector (DAD) at 200 nm. By assuming that only negligible amounts of other intermediate products were formed (e.g., and ) [ 32 ], the selectivity to nitrogen ( ) was calculated as follows: where the selectivity to ammonium ( ) and nitrite ( ) are based on the measured and concentrations and calculated as follows: and with the measured initial concentration and the measured final concentration of nitrate ( ). The NPs size effect on activity was evaluated by calculating TOF values for each catalyst.…”
Section: Methodsmentioning
confidence: 99%
“…For example, Hamid et al developed a variety of supported Pd/Sn bimetallic catalysts, which showed good reactivity in the reduction catalysis of NO 3 – . Pd/Sn with different supports (NBeta, NZSM-5, and Red mud) all showed high kinetic rate constants and high selectivity. Huang et al encapsulated only one Au nanoparticle below 10 nm in the TiO 2 –ZrO 2 shell to form a nanoreactor with a yolk–shell structure. During the thermal treatment or the reduction catalysis of 4-nitrophenol, the Au nanoparticles inside the mesoporous shell showed significant catalytic activity and antiaggregation properties.…”
Section: Environmental Catalytic Applicationsmentioning
confidence: 99%
“…Therefore, improving the selectivity of N 2 is essential for the nitrate reduction. In recent, nitrate could be high-selectively reduced to N 2 by ion exchange/catalysis integrated process and nanocrystalline materials supported bimetallic catalyst reduction process; however, these process were relatively expensive for practical application. Thus, simplification of the denitrification process with high N 2 selectivity of nitrate reduction has many advantages in economic and efficient aspects.…”
Section: Introductionmentioning
confidence: 99%